Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2147/cia.s268118
|View full text |Cite
|
Sign up to set email alerts
|

<p>In-Hospital Postoperative Pneumonia Following Geriatric Intertrochanteric Fracture Surgery: Incidence and Risk Factors</p>

Abstract: Purpose The in-hospital death rate in cases of hip fracture ranges from 6% to 10%. Pneumonia is a serious complication for hip fracture patients that contributes to longer hospital stays and higher mortality rates; however, the prevalence and risk factors are not well established. To address this issue, the present study investigated the incidence of and risk factors for in-hospital postoperative pneumonia (IHPOP) following geriatric intertrochanteric fracture surgery. Patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…The introduction of the original extramedullary sliding screw device in the 1950s revolutionized the treatment of intertrochanteric fractures, and it quickly became the standard for the acute treatment of intertrochanteric fractures (7). However, in the 1990s, the head bone marrow nail became popular despite a lack of solid evidence of its superior performance (8).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of the original extramedullary sliding screw device in the 1950s revolutionized the treatment of intertrochanteric fractures, and it quickly became the standard for the acute treatment of intertrochanteric fractures (7). However, in the 1990s, the head bone marrow nail became popular despite a lack of solid evidence of its superior performance (8).…”
Section: Introductionmentioning
confidence: 99%
“…Noordin et al 21 found that octogenarian patients who underwent dynamic hip screw fixation for intertrochanteric femur fractures had a higher rate of postoperative complications (25%) and 1-year mortality (22%) than those younger than 80 years (4% and 8%, respectively). Similarly, in a study by Zhao et al 22 age greater than 82 years was found to be an independent risk factor of in-hospital postoperative pneumonia after surgical management of intertrochanteric femur fractures. In addition, Matityahu et al 23 found that octogenarians who sustained operatively managed pelvic fractures had a higher risk of mortality and complications than the nonoctogenarian geriatric population.…”
Section: Discussionmentioning
confidence: 72%
“…Although the age cutoff for high risk of POP following geriatric hip fracture surgery was variable, three studies reported that patients aged >80 years were at a particularly high risk for POP. 14 , 16 , 17 Furthermore, the risk for POP increases with age, and older patients who developed POP had longer hospital stays and higher mortality rates. 18 This suggests that the elderly, especially those over the age of 80 years, are more likely to develop POP after hip fracture surgery and thus require special attention.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that males tend to have poorer health and more comorbidities compared to females. 17 …”
Section: Discussionmentioning
confidence: 99%